ANALYSIS OF IMPROVING THE RELIABILITY OF A 20 KV DISTRIBUTION NETWORK SYSTEM USING THE HOT-SPOT IDENTIFICATION METHOD IN THE CUSTOMER SERVICE UNIT (ULP) OF WOHA - Ilham Nuzul Firman; Hamdani; Hikmatul Fadhilah Sianipar (Journal of Information Technology, computer science and Electrical Engineering, 2025)
PT. PLN (Persero) is a company with an extensive distribution network system, which continues to expand in terms of the number of distribution networks. This company is known for its excellent efforts in improving the quality of service to its customers, particularly in meeting the electricity needs of customers in the West Nusa Tenggara region. With the existing distribution system network, reliability analysis can be determined by assessing the system's quality in relation to disruptions that occur. To improve the quality of electricity distribution, the performance of the distribution network system is a key aspect that will always be maintained to ensure electricity is delivered to customers. In enhancing the quality of the distribution system, the calculation of reliability indices, based on the average interruption frequency (SAIFI) and the average interruption duration (SAIDI), serves as a reference for the reliability of the distribution network.